Biogeographical diet variation within and between the rabbitfishes Siganus corallinus, Siganus doliatus, Siganus trispilos and Siganus virgatus - Salvador Zarco‐Perello; Storm B. Martin; Andrew Hoey (Ecology and Evolution, 2024)
Abstract Feeding habits of herbivorous fishes play an important role in shaping the form and function of coastal marine ecosystems. Rabbitfishes (Siganidae) are important consumers of macroalgae on Indo‐West Pacific coral reefs. However, it is unclear how their diet varies among and within species at biogeographical scales, casting doubt on their precise functional roles across different regions. The present study assessed the inter‐ and intra‐specific diet variation of four rabbitfishes (Siganus trispilos, Siganus corallinus, Siganus virgatus and Siganus doliatus) factored by morphological relatedness among populations from Ningaloo Reef (western Australia), the Great Barrier Reef (GBR, eastern Australia) and the Yaeyama Islands (Okinawa Prefecture, Japan). Results showed that the region had a strong effect on diet, effectively reducing the expected effect of morphologic similitude. While intra‐specific differences were only significant when populations inhabited different regions; interspecific differences were not as predicted, with different morphotypes having similar diets when populations inhabited the same regions. Rabbitfishes consumed more corticated and filamentous macroalgae on the GBR, more foliose and membranous macroalgae at the Yaeyama Islands, and more leathery macroalgae at Ningaloo Reef. The findings indicate that rabbitfishes have high diet plasticity, and hence their functional role as mediators of competition between macroalgae and corals can change across biogeographic regions. Local context is therefore important when assessing the diet and functional role of herbivorous fishes. As climate change unfolds, shifts in the distribution, trophic behaviour and function of species are expected, making the study of trophic plasticity more important.